2004
DOI: 10.1128/iai.72.12.7140-7146.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Defensin from the Sand Fly Phlebotomus duboscqi Induced by Challenge with Bacteria or the Protozoan Parasite Leishmania major

Abstract: Antimicrobial peptides are major components of the innate immune response of epithelial cells. In insect vectors, these peptides may play a role in the control of gut pathogens. We have analyzed antimicrobial peptides produced by the sand fly Phlebotomus duboscqi, after challenge by injected bacteria or feeding with bacteria or the protozoan parasite Leishmania major. A new hemolymph peptide with antimicrobial activity was identified and shown to be a member of the insect defensin family. Interestingly, this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
124
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 39 publications
5
124
0
2
Order By: Relevance
“…For example, gambycin is an antimicrobial peptide which has been isolated from the Anopheles vector; it is induced during early and late stages of malaria and is lethal for Plasmodium berghei ookinetes (Vizioli et al 2001). A Phlebotomus duboscqui defensin has exhibited anti-parasite activity, specifically against Leishmania major promastigote forms (Boulanger et al 2004). A complement system-like protein (TEP-1) from the Anopheles gambiae mosquito has promoted destruction of P. berghei stages in the insect's mid-gut (Blandin et al 2004).…”
Section: Ph the Protein Was Partially Purified By Gel Filtration Chrmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, gambycin is an antimicrobial peptide which has been isolated from the Anopheles vector; it is induced during early and late stages of malaria and is lethal for Plasmodium berghei ookinetes (Vizioli et al 2001). A Phlebotomus duboscqui defensin has exhibited anti-parasite activity, specifically against Leishmania major promastigote forms (Boulanger et al 2004). A complement system-like protein (TEP-1) from the Anopheles gambiae mosquito has promoted destruction of P. berghei stages in the insect's mid-gut (Blandin et al 2004).…”
Section: Ph the Protein Was Partially Purified By Gel Filtration Chrmentioning
confidence: 99%
“…Nevertheless, a close association has been observed between T. rangeli KP1(+) and vectors from the prolixus group (which includes Rhodnius prolixus and Rhodnius neglectus) and between T. rangeli KP1(-) and vectors from the pallescens group (including Rhodnius pallescens, Rhodnius colombiensis and Rhodnius ecuadoriensis) , Urrea et al 2005. Recent parasite-vector interaction studies have shown a trypanolytic factor in R. prolixus hemolymph impeding the development of T. rangeli KP1(-) strains isolated from R. pallescens, R. colombiensis and R. ecuadoriensis (Sánchez et al 2005).It has been stated that immune peptide and protein production in malaria, leishmaniasis and trypanosomiasis vectors could play an important role in limiting parasite infection (Boulanger et al 2001(Boulanger et al , 2002a(Boulanger et al , 2004; this fact could explain different aspects related to these parasitosis' vectorial ability (Boulanger et al 2002b(Boulanger et al , 2006 Most studies carried out on different vectors have led to identifying inducible peptides and proteins as a response to parasite infections. For example, gambycin is an antimicrobial peptide which has been isolated from the Anopheles vector; it is induced during early and late stages of malaria and is lethal for Plasmodium berghei ookinetes (Vizioli et al 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…hemolymph, apidaecin was produced which resulted in inhibitory effects on Gram-positive bacteria (23). Another study revealed that the stimulation of sand fly, Phlebotomus duboscqi, by injected protozoan parasite or bacteria triggered the release of defensin family peptides with anti-bacterial activity in their hemolymph (24). It was reported that the presence and activity of antimicrobial cecropin proteins in Galleria mellonella hemolymph after an 18-hour infection by Pseudomonas aeruginosa (an insect pathogenic bacteria species) and E. coli (a non-pathogenic strain), the peak activity of the insect immune system was observed up to 48 hours after injection (25).…”
Section: Discussionmentioning
confidence: 99%
“…Las fracciones 1, 3 y 4 (figura 5) presentaron diferencias significativas al ser comparadas con las mismas fracciones obtenidas de hemolinfa control sin reto, pero inyectadas con PBS; este aumento en la actividad leishmanicida puede deberse a la inducción de proteínas o péptidos que fueron inducidos por el reto inmunológico y no por el trauma causado en la larva. La inducción de PAMs en insectos en presencia de parásitos de Leishmania ha sido registrada en Phlebotomus duboscqi (Boulanger et al 2004). …”
unclassified